Multidisciplinary perspectives on cross-border trade and business - Asmat Nizam Abdul Talib; Norhayati Zakaria, 1969-; Abdul Latif, Samshul Amry, 1978- (Advances in business strategy and competitive advantage., 2022)
"Cross border business transactions have become increasingly important due to new norms of doing business so this book captures the multi-faceted outlook on international business phenomena particularly when cross border businesses were severely affected by the worldwide pandemic"--